Nominalisme dan Gugatannya terhadap Universalitas dalam Pemikiran Realisme Metafisik - Suryosumunar, John Abraham Ziswan; Devitasari, Erliyana (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2024)
This article is based on qualitative research in the field of philosophy. The data used in this study are literature data related to the research object. The method of philosophical hermeneutics is used in the analysis process by placing the perspective of nominalism as the formal object, while the view of universality from the perspective of metaphysical realism as the material object. The results of this research are as follows: 1) Nominalism is a metaphysical stream that rejects abstract and universal entities, unlike the perspective of metaphysical realism which refers to the Platonic scheme. 2) Nominalism places concepts as theoretical constructions that must correspond to concrete experience, rejecting the universal ideas held by realism. Nominalism emphasizes that the attributes of concrete objects originate from the objects themselves, not from universal entities. 3) Nominalism is related to language issues. It emphasizes theoretical simplicity and rejects excessive entities in articulating the similarity between objects.